Penerapan Etika Bisnis Islam di Kalangan Mahasiswa FEBI UINSU dalam Transaksi Jual Beli Online - Anisah, Azizah; Fadhila, Eka; Pasaribu, Indriani; Sigalingging, Sinarta; Hayati, Fitri (Teewan Journal Solutions, 2025)
The application of Islamic business ethics in online buying and selling transactions among students Febi of the State Islamic University of North Sumatra (UINSU) is an important concern, especially considering the potential conflict between the principles of Islamic business ethics and the practices carried out. This research uses a qualitative approach with a case study method. Data were obtained through in- depth interviews and document analysis. The results showed that the majority of students understand the basic principles of Islamic business ethics, such as honesty, fairness, transparency, and responsibility. However, the implementation of these principles has not been fully consistent, especially in the aspects of pricing, disclosing product information, and handling consumer complaints. The main factors influencing the level of implementation of Islamic business ethics are the level of religious knowledge, economic motivation, and the influence of the social environment. Recommendations are given to improve Islamic business ethics education through formal curriculum and extracurricular programs. This research aims to contribute to understanding the application of Islamic values in online buying and selling activities, while encouraging the creation of transactions that are in accordance with sharia principles and provide benefits for all parties.